Experimental study and numerical simulation on the structural and mechanical properties of Typha leaves through multimodal microscopy approaches. (January 2018) - Liu, Jingjing; Zhang, Zhihui; Yu, Zhenglei; Liang, Yunhong; Li, Xiujuan; Ren, Luquan
Graphical abstract: Typha leaf is an ideal bionic prototype utilized for lightweight design. In this paper, the structure and mechanical properties of leaves were investigated under Micro-CT, SEM, mechanical tests and simulation analysis. The results showed that the internal rib structure of Typha leaf effectively enhances the resistance to compression and bending deformation. Highlights: The three-dimensional macroscopic morphology and microstructure of Typha leaf were analyzed by means of Micro-CT and SEM. Effect of internal structure on mechanical behavior of leaves was studied by compression and bending tests. Inspired by the structure in leaf, three models with different internal structures were established. Effect of internal structure on the mechanical properties was verified using the nonlinear ﬁnite element code LS-DYNA. Abstract: The Typha leaf, with special multi-level structure, low density and excellent mechanical properties, is an ideal bionic prototype utilized for lightweight design. In order to further study the relationship between the structure and mechanical properties, the three-dimensional macroscopic morphology of Typha leaves was characterized by micro computed tomography (Micro-CT) and its internal microstructure was observed by scanning electron microscopy (SEM). The combination of experimental and computational research was carried out in this paper, to reveal and verify the effect of multi-level structure on the mechanical properties. A universal testing machine and a self-developed mechanical testing apparatus with high precision and low load were used to measure the mechanical properties of the axial compression and lateral bending of the leaves, respectively. Three models with different internal structures were established based on the above-mentioned three-dimensional morphologies. The result demonstrated that the structure of partitions and diaphragms within the Typha leaf could form a reinforcement ribs structure which could provide multiple load paths and make the process of compression and bending difficult. The further nonlinear finite element analysis through LS-DYNA proved that internal structure could improve the ability of the models to resist compression and deformation. The investigation can be the reference for lightweight thin-walled structure design and inspire the application of the bionic structural materials.